Slab pileup in the mantle transition zone and the 30 May 2015 Chichi‐jima earthquake - Robert W. Porritt; Shoichi Yoshioka (Geophysical Research Letters)
Abstract The 30 May 2015 Chichi‐jima M8 earthquake is one of the largest deep focus earthquakes ever recorded and its depth of 682 km puts it near the base of the mantle transition zone. Before source mechanisms and slip models of this earthquake can be reliably assessed, a better understanding of the tectonic setting and structures of the region near the origin is required. Here we present evidence from receiver functions, a method of isolating subsurface material contrast with converted seismic waves, that the earthquake initiated within the upper mantle transition zone, above a significantly depressed 660 km phase boundary. Additionally, we observe multiple conversions within and below the transition zone, which we associate with seismic waves passing into and out of segments of the subducting Pacific plate. From this, we infer slab material is piling up at the base of the transition zone and segments are penetrating into the lower mantle.